2020
DOI: 10.1007/s42000-020-00185-y
|View full text |Cite
|
Sign up to set email alerts
|

Minding the gap between cortisol levels measured with second-generation assays and current diagnostic thresholds for the diagnosis of adrenal insufficiency: a single-center experience

Abstract: Purpose The current cut-offs for the diagnosis of adrenal insufficiency (AI) have been established using outdated immunoassays. We compared the cortisol concentrations measured with Roche Cortisol I (R1), the newly available Roche Cortisol II (R2), and liquid chromatography tandem mass spectrometry (LC-MS/MS), the gold standard procedure to measure steroids in patients undergoing the corticotropin (ACTH) test. Methods We enrolled 30 patients (age 47 ± 21 years) referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…We have shown that the threshold cortisol response to CST of 14 to 15 μg/dL in a large group of patients with suspected secondary adrenal insufficiency is comparable to the 18 μg/dL cutoff previously used. Grassi et al also found lower cortisol cutoff values of 12.7 and 13.3 μg/dL using Elecsys II and LC-MS/MS assays, respectively [ 37 ]. Cutoff values 30 minutes after ACTH stimulation have been proposed to be 14.9 μg/dL for LC-MS/MS and 16 μg/dL for Elecsys II based on the 2.5 th centile in healthy controls [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the threshold cortisol response to CST of 14 to 15 μg/dL in a large group of patients with suspected secondary adrenal insufficiency is comparable to the 18 μg/dL cutoff previously used. Grassi et al also found lower cortisol cutoff values of 12.7 and 13.3 μg/dL using Elecsys II and LC-MS/MS assays, respectively [ 37 ]. Cutoff values 30 minutes after ACTH stimulation have been proposed to be 14.9 μg/dL for LC-MS/MS and 16 μg/dL for Elecsys II based on the 2.5 th centile in healthy controls [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The new cutoffs varied from 14 to 15 µg/dL and were based on comparisons of 110 subjects using the Elecsys Cortisol I assay with a cutoff of 18 µg/dL as the standard. Others have proposed cutoffs of 12.7 µg/dL with the Roche Cortisol II assay and 13.3 µg/dL with LC-MS/MS [ 2 ]. A Roche-sponsored study also showed good agreement between the Cortisol II assay and LC-MS/MS methods at 3 separate institutions on 3 different instruments [ 3 ].…”
mentioning
confidence: 99%
“…Similarly, the recent introduction of more specific cortisol assays results in lower cortisol concentrations and this may increase the number of patients diagnosed with adrenal insufficiency. The medical community should quickly adopt the new criteria, as this could lead to misdiagnosis and overtreatment in patients suspected of hypocortisolism (39).…”
Section: What and How To Measurementioning
confidence: 99%